2019
DOI: 10.1002/celc.201900729
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Electrochemical Properties of 1,1,2,2‐Tetrafluoroethyl‐2,2,3,3‐Tetrafluoropropyl Ether as a Co‐Solvent for High‐Voltage Lithium‐Ion Electrolytes

Abstract: Although high-voltage positive electrode materials for high energy density lithium-ion batteries have gained a great attention, the lack of compatible electrolytes with sufficiently high oxidative stability to deliver an excellent cycling ability restricts their practical application. Fluorinated solvents are considered as promising candidates for high-voltage electrolyte solvents. In this study, we select 1,1,2,2-tetrafluoroethyl-2,2,3,3tetrafluoropropyl ether (TTE) with a high boiling point, low cost, and go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…However, the FEC‐EMC electrolyte solution suffers from the oxidative decomposition around 5.0 V vs Li/Li + . When the fluorinated ether, HFPM or TTE, being added into the FEC‐EMC electrolyte solution, the oxidation potential of both FEC‐EMC‐HFPM and FEC‐EMC‐TTE electrolyte solutions increases to 5.5 V vs Li/Li + , which is in accordance with the DFT calculation results and our previous literature's reports 33,34 . On the cathodic scan, the electrochemical reduction of the FEC‐EMC‐TTE electrolyte starts at 3.5 V, which is prior to that of the FEC‐EMC‐HFPM electrolyte.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…However, the FEC‐EMC electrolyte solution suffers from the oxidative decomposition around 5.0 V vs Li/Li + . When the fluorinated ether, HFPM or TTE, being added into the FEC‐EMC electrolyte solution, the oxidation potential of both FEC‐EMC‐HFPM and FEC‐EMC‐TTE electrolyte solutions increases to 5.5 V vs Li/Li + , which is in accordance with the DFT calculation results and our previous literature's reports 33,34 . On the cathodic scan, the electrochemical reduction of the FEC‐EMC‐TTE electrolyte starts at 3.5 V, which is prior to that of the FEC‐EMC‐HFPM electrolyte.…”
Section: Resultssupporting
confidence: 89%
“…Pham et al achieved the maximum capacity (>230 mAh g −1 ) and good capacity retention (95% after 100 cycles) of NCM811 electrodes with charging to 4.5 V in a non‐flammable electrolyte with propylene carbonate (PC) and fluorinated linear carbonates 31 . In our previous work, 33,34 we found that the partially fluorinated ethers, such as 1,1,1,3,3,3‐hexafluoroisopropyl methyl ether (HFPM) and 1,1,2,2‐ tetrafluoroethyl‐2,2,3,3‐tetrafluoropropyl ether (TTE), as a co‐solvent of fluoroethylene carbonate (FEC)‐based electrolytes, demonstrated not only a good cycle stability in high‐voltage LNMO electrodes but also a good wettability with the separator. Here, we investigate these fluorinated ethers including TTE and HFPM as a co‐solvent for FEC‐based electrolytes to decrease electrolyte oxidative decomposition during NCM811 cycling process.…”
Section: Introductionmentioning
confidence: 95%
“…Hence, although in small quantities, the lithium ions adequately adhere in the vicinity of the graphite and NMC interfaces, attributed to the ability of TFE to maintain a high concentration gradient due to its high polarizability and low electronegativity (Scheme ). , …”
mentioning
confidence: 99%
“…Recently, fluorine-containing solvent such as 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), has been proposed as a co-solvent for the electrolytes of high-voltage lithium-ion batteries. [44] TTE-containing electrolytes exhibit a high oxidative stability up to 5.5 V because of the high electronegativity and low polarizability of fluorine atoms in TTE so the electrochemical oxidation of fluorinated solvents is difficult. In addition, a few studies have also been reported for using fluorine-containing solvents in electrolytes of batteries to reduce their self-discharge.…”
Section: Introductionmentioning
confidence: 99%